Stress, anxiety and depression in 1466 pregnant women during and before the COVID-19 pandemic: a Dutch cohort study - S. J. M. Zilver; B. F. P. Broekman; Y. M. G. A. Hendrix; R. A. de Leeuw; S. V. Mentzel; M. G. van Pampus; C. J. M. de Groot (Taylor & Francis Group, 2021)
Objective The coronavirus disease (COVID-19) pandemic has negatively affected many people's mental health with increased symptoms of stress, anxiety and depression in the general population. Anxiety and depression can have negative effects on pregnant women and result in poor neonatal outcomes. Therefore, we analyzed stress, anxiety and depression in pregnant women during the COVID-19 pandemic. Materials and methods Cohort study of pregnant women during COVID-19 compared to pregnant women before COVID-19. Pregnant women were recruited through social media platforms from 21 May 2020 to 22 June 2020. Pregnant women ≥ 18 years of age, who master the Dutch language were included. The Hospital Anxiety and Depression Scale (HADS) and the Perceived Stress Scale (PSS-10) were analyzed. Demographic features were summarized using descriptive statistics. Possible differences in demographic variables between groups were compared using Mann Whitney U test and Chi-squared test. Significant demographic differences between groups were controlled for using logistical regression analysis or an independent one-way analysis of covariance. Results Thousand hundred and two pregnant women completed the questionnaires during COVID-19, and 364 pregnant women before COVID-19. We found no differences in clinically high levels of anxiety (HADS-A ≥ 8) and depression (HADS-D ≥ 8) in women during COVID-19 (19.5% and 13.2%, respectively) and women before COVID-19 (23.1% and 15.7%, respectively). A question was implemented whether participants related their stress level to COVID-19. Women who related their stress to the COVID-19 pandemic reported significantly higher overall stress levels on the PSS-10 compared to women with stress unrelated to COVID-19 (mean, 15.62; standard deviation [SD], 6.44 vs. mean, 10.28; SD, 5.48; p < 0.001). Conclusion In contrast to previous studies, COVID-19 did not increase anxiety and depression levels in Dutch pregnant women. Women who related their perceived stress to the COVID-19 pandemic experienced higher stress levels than women who did not relate their stress to the COVID-19 pandemic, suggesting that interventions that specifically aim to reduce COVID-19 stress, may help to reduce overall stress levels in pregnant women during the pandemic.